Differential affinities of simian virus 40 large tumor antigen for DNA. - Oren, M (1980)
The binding of simian virus 40 (SV40) large tumor antigen (T antigen) to DNA was analyzed by using the salt-sensitive affinities of the protein for various DNAs immobilized on cellulose. At least two types of interactions could be distinguished that differed in their stability. Higher salt concentrations were required to elute T antigen from SV40 DNA than from calf thymus DNA; and even greater salt concentrations were required for the lution of T antigen from multiorigin SV 40 DNA compared to wild-type SV40 DNA. This would indicate that T antigen can bind weakly or strongly to DNA, depending on the DNA sequence. It was also found that a greater proportion of rapidly labeled or newly synthesized T antigen binds more efficiently and tightly to multiorigin SV40 DNA than to long-labeled or older forms of T antigen. This approach can be utilized not only to distinguish between different forms of T antigens which vary in their affinities for DNA but also for rapidly obtaining highly enriched T antigen preparations.